PROYEK PENGEMBANGAN PRODUK MAKANAN TRADISIONAL DENDENG BALADO KEMASAN “NAN TARASO” - Ramadhan, Anwar; Games, Donard (ANALISIS, 2022)
New product development has become a way to enhance business growth. In this case, “Dendeng balado” as one of the Mnangkabau traditional cuisines that can be transformed into new type of products by using the concept of new product development. The purpose of this paper is to examine entrepreneurial activities from the implementation of new product development by producing new type of “dendeng balado” (beef jerky): dendeng balado as an instant food. This project was carried out through several stages, starting from problem solving concept development followed by idea validation and market validation. Business strategies were formulated by using business model canvas in order to make certain that this product can be accepeted by target markets. It was found that brand new "Nan Taraso" has succesfully attracted potential target markets as they like the new packaging including its colour and design. I terms of commercialization phase, it was found that it would have been better for this product to be sold to travellers and those who see this product as “oleh-oleh” from West Sumatra. His can be considered re-target market that signifies the importance of business strategies and market dynamics.